2021
DOI: 10.1002/saj2.20274
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping kura clover with prairie cordgrass grown on a marginal land enhanced soil carbon and nitrogen fractions

Abstract: Prairie cordgrass (PCG) (Spartina pectinata Link) has been the focus of much scientific attention recently for use in biofuel applications, as it grows well on marginal lands that are unsuitable for row crops. This study investigated how the intercropping of kura clover (KC) (Trifolium ambiguum M. Bieb) with PCG for 8 yr affects soil carbon (C) and nitrogen (N) fractions compared with N fertilization on marginally yielding croplands in South Dakota. This study was initiated in 2011 with five treatments: interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…These sugars fuel soil microbial respiration, ultimately leading to the release of CO 2 (Adetunji et al., 2020; Zhang et al., 2021). The results from our study are consistent with other studies from the same experiment: Abagandura and Kumar (2021) reported higher C mineralization, and Abagandura et al. (2020) observed relatively higher CO 2 emissions with PCG‐KC intercropping.…”
Section: Discussionsupporting
confidence: 93%
“…These sugars fuel soil microbial respiration, ultimately leading to the release of CO 2 (Adetunji et al., 2020; Zhang et al., 2021). The results from our study are consistent with other studies from the same experiment: Abagandura and Kumar (2021) reported higher C mineralization, and Abagandura et al. (2020) observed relatively higher CO 2 emissions with PCG‐KC intercropping.…”
Section: Discussionsupporting
confidence: 93%